Magnetic surgical marker navigation for excision of non-palpable ultrasound visible breast lesions: first 200 cases in a French cancer center - Vivien Ceccato; Lauren Wallaert; Sophie Michel; Thomas Gaillard; Noémie Girard; Lauren Darrigues; Léa Pauly; Elodie Gauroy; Emilie Raimond; Imane Menouer; Olivier Graesslin; Julie Rosa; et al. (Scientific Reports)
Abstract Wire guided localization is widely used as the standard method of pre-operative localization of breast lesions. The aim was to assess outcomes following the introduction of a novel non-wire guided, magnetic surgical marker navigation system. A prospective study between May 2022 and June 2023 established a data base of the first 200 procedures performed using the Sirius Pintuition GPS Detect magnetic marker. The primary outcome measures were the successful excision of the target lesion and retrieval of the magnetic marker. The primary lesion was excised and the magnetic marker was retrieved in all 200 procedures. In 17 procedures (8.5% of the total sample), the magnetic marker was dislodged during surgery; however, the primary lesion was still effectively excised with clear margins without the need for an additional procedure or radiologic assistance. The re-excision rate to achieve margin clearance was 9%. Insertion of the marker was classified as “easy” and “in contact with the target” by the radiologist in all cases (100%). This study has shown that surgical marker navigation reliably localizes lesions and is associated with low re-excision rates. We also perceived improvement in theater planning.